The Ahlu Shuffah Learning System That Formed The Best Generation During The Time Of The Prophet Muhammad Saw - Maulidani Ulfah; Muhammad Zalnur; Fauza Masyhudi (Penerbit Hellow Pustaka, 2024)
Education is a very important thing in life. A person can be said to be human if he has knowledge. The phenomenon that occurs in education today, especially in Indonesian Education, can still be said to be less effective, because there are still many shortcomings that result in unemployment, conflict, and crime that occurs everywhere (loss of adab). So this article was written with the aim of exploring knowledge about Education that had previously been successful in its time which was able to form the best generation of civilization which could change the lives of sinful people into responsible high officials and make poor people into great scholars who are famous until now. The concept of education is Ahlu Suffah which was founded by the Prophet Muhammad SAW. Ahlu Suffah is one proof of how education should be applied in everyday life. so that the knowledge gained can become sweet fruit for yourself for others.